Upconversion nanoparticles: Recent strategies and mechanism based applications - Dubey, Neha; Chandra, Sudeshna (Journal of rare earths, 2022)
Upconversion nanoparticles (UCNPs) doped with lanthanides can convert near-infrared excitation into UV and visible emissions. Because of their relatively high emission efficiency, UCNPs are appealing materials for use in a variety of sectors. UCNPs are known for low auto-fluorescence, excellent chemical and thermal photo-stability, deep tissue penetration, exceptional biocompatibility, low toxicity, color purity, and ease of surface functionalization. In this review, we explain a few recent strategies to boost the efficiency and luminescence of upconversion nanoparticles and minimize quenching by fabricating them as core/shell, nanofibers, or heavily doped lanthanides. Applications of UCNPs in drug delivery, Photodynamic therapy (PDT), biosensors, bioimaging, and optogenetics are also discussed along with their mechanism of action. Our motivation for this review is to understand the working mechanism of UCNPs and their applications in various fields. [Display omitted]